Phytochemicals in Agriculture and Food (IntechOpen, 2024)
Plants employ strategies to tackle the challenges in their ecosystems, notably by synthesizing secondary metabolites. These unique molecules aid plants in adapting to their surroundings and are key sources of active pharmaceutical ingredients. Recent discoveries have identified multiple phytochemicals in different species, enhancing the medicinal and nutritional worth of fruits, seeds, and cereals. These compounds are celebrated for their functional and nutraceutical attributes. This book provides a comprehensive overview of phytochemicals in agriculture and food.